Pengaruh Variabel Tangible Terhadap Kepuasan Pengguna Kapal Putri Kembang Dadar - Novy Yanti; Yusleli Herawati; Sari Lestari Zainal Ridho (Jurnal Aplikasi Manajemen dan Bisnis, 2022)
This study aims to determine the effect of tangible variable on the service quality of Putri Kembang Dadar on customer satisfaction. The quality of service studied consists of tangible variable and several other variables. Data were collected using a questionnaire with a population of 60 respondents who used the ship's services. This research uses multiple linear regression analysis technique. The results of this study indicate that there is a partially significant effect on tangible variable with a significance result of 0.001 < 0.05.